ABREU, Caio Fernando. Poesias nunca lidas de Caio Fernando Abreu. Org. Letícia da Costa Chaplin e Márcia Ivana de Lima e Silva. Rio de Janeiro: Record, 2012. DOI: 10.5212/MuitasVozes.v.1i2.0011 (Muitas Vozes, 2013)
.